Digital Fiscal Surveillance : Implementasi Tapping Box dalam Optimalisasi Pajak Restoran - Bambang Suprianto; Jiwa Riwayanti (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
This study aims to analyze the implementation of digital fiscal surveillance through the use of tapping boxes in optimizing restaurant tax collection in Ogan Komering Ilir Regency. The research employs a descriptive qualitative approach with data collected through in-depth interviews, observations, and documentation studies. Data were analyzed using the reduction, presentation, and conclusion drawing model proposed by Miles, Huberman, & Saldaña. The findings reveal that the implementation of tapping boxes enhances transparency and accountability in restaurant tax collection by providing real-time transaction data. The devices strengthen taxpayer compliance, particularly in terms of instrumental compliance, as the risk of detection for non-compliance increases significantly. Nevertheless, several challenges remain, including resistance from some restaurant owners, limited internet infrastructure, and the need for regular device maintenance. Overall, tapping boxes hold significant potential for optimizing restaurant tax revenues at the regional level, provided that local governments improve socialization, technical support, and digital infrastructure readiness.